The notch signaling regulates CD105 expression, osteogenic differentiation and immunomodulation of human umbilical cord mesenchymal stem cells. - Tao Na; Jing Liu; Kehua Zhang; Min Ding; Bao-Zhu Yuan (PLoS ONE, 2015)
Mesenchymal stem cells (MSCs) are a group of multipotent cells with key properties of multi-lineage differentiation, expressing a set of relatively specific surface markers and unique immunomodulatory functions. IDO1, a catabolic enzyme of tryptophan, represents a critical molecule mediating immunomodulatory functions of MSCs. However, the signaling pathways involved in regulating these key properties still remain elusive. To investigate the involvement of Notch signaling as well as other potential signaling pathway(s) in regulating these critical properties of MSCs, we treated human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) with γ-secreatase inhibitor I (GSI-I), which inhibits both Notch signaling and ubiquitin-proteasome activities. It was shown that the GSI-I treatment resulted in apoptosis, reduced expression of surface markers CD73, CD90 and CD105, reduced osteogenic differentiation, and reduction of the hUC-MSCs-mediated suppression of Th1 lymphocyte proliferation and the IFN-γ-induced IDO1 expression. Through distinguishing the effects of GSI-I between Notch inhibition and proteasome inhibition, it was further observed that, whereas both Notch inhibition and proteasome inhibition were attributable to the reduced CD105 expression and osteogenic differentiation, but not to the induced apoptosis. However, Notch inhibition, but not proteasome inhibition, only contributed to the significant effect of GSI-I on Th1 proliferation probably through reducing IDO1 promoter activity. In conclusion, the Notch signaling may represent a very important cell signaling capable of regulating multiple critical properties, especially the immunomodulatory functions of MSCs.